Pengaruh Green Hotel Terhadap Keputusan Menginap Wisatawan di Hotel Mercure bali Nusa Dua - Yusrin Yusrin; I Nyoman Jamin Ariana; I Nyoman Tri Sutaguna (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2022)
Sustainable tourism is tourism that takes full account of current and future economic, social and environmental impacts. This study aims to determine the perceptions of tourists on the application of green hotels at the Mercure Bali Nusa Dua hotel to determine the effect of green hotels on tourists' decision to stay at the Mercure Bali Nusa Dua hotel. The technique of collecting data was carried out by observation, interviews, documentation, literature study, and questionnaires. The data analysis technique used in this research is descriptive statistical analysis consisting of a Likert scale, validity test, reliability test, simple linear regression analysis, correlation analysis, and determination analysis and hypothesis testing is (t-test) with an error rate of 5 percent. The result of this research is that tourists perceive the implementation of green hotels at the Mercure Bali Nusa Dua hotel in the very good category with an average of 4.30 percent according to the tourists' views. Simple linear regression analysis, analysis between green hotels and tourists' decisions to stay overnight obtained the equation Y = 6.491 + 0.425X. From the results of the correlation analysis shows that the relationship between the two variables is very high with a correlation coefficient of 0.864. The coefficient of determination of value is 74 percent and the remaining 26 percent is influenced by other variables. By using the t-test statistical analysis proves that a significant level of 5 percent is accepted because the t value (16,999) is greater than the t-table value (1,984), in other words green hotels positively and significantly influence tourists' decisions to stay at hotels. Mercure Bali Nusa Dua. Keywords: Green Hotel, Tourist Decision to Stay.